The Relationship between Team Performance Pressure and Unethical Pro-Team Behavior: The Mediating Role of Collective Moral Disengagement - Nila Sari Puspita Ningsi Latif; Etik Darul Muslikah; Eben Ezer Nainggolan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The increasing reliance of organizations on team-based work systems has intensified the pressure placed on team members to achieve, maintain, or improve collective performance targets. While such pressure is often assumed to enhance productivity, it may also create conditions under which team members are willing to violate ethical norms to protect or benefit their team, a phenomenon labeled unethical pro-team behavior (UPTB). This study examined the relationship between team performance pressure (TPP) and UPTB, as well as the mediating role of collective moral disengagement (CMD) in that relationship. A quantitative correlational design with a cross-sectional survey was employed, involving 357 employees working in teams across public and private organizations in East Java, Indonesia, selected through quota sampling. Data were collected using modified Likert-type instruments adapted from established scales and analyzed using PROCESS Macro Model 4 with 5,000 bootstrap resamples. Results indicated that TPP had a significant positive total effect on UPTB (B = 0.612, p < 0.001), supporting Hypothesis 1. Mediation analysis showed that TPP significantly predicted CMD (B = 0.562, p = 0.003), and CMD significantly predicted UPTB after controlling for TPP (B = 0.487, p < 0.001). The indirect effect of TPP on UPTB through CMD was significant (effect = 0.274, 95% CI [0.090, 0.450]), while the direct effect remained significant (B = 0.338, p < 0.001), indicating partial mediation and supporting Hypothesis 2. These findings extend Social Cognitive Theory and Moral Disengagement Theory to the team level, demonstrating that performance pressure shapes unethical behavior both directly and through collectively shared moral rationalization. Practical implications for performance management, team leadership, and human resource interventions are discussed.